SOSIALISASI DAN PELATIHAN BAGI ANAK – ANAK DI RUMAH BELAJAR GERAKAN AMSAL 3, TEMA : ANAK CERDAS INDONESIA MAJU - Adolfina Putnarubun; Roberthair Suripatty; Arce Yulita Ferdinandus; Ratna R. Pakpahan; La Ode Rajamin; Saskia Olivia Silvana Fugida; Leidy Damima; Johan F.H. Lakburlawal; Sadaria, Sadaria; Yuntari Bria; Regina Wakim; Gilya Gamelia Uneputty; Marice Mambrasar; Deleven Echi Sikirit (Yayasan Nusantara Hasana Berdikari, 2026)
Children's character development is a crucial aspect in shaping a quality future generation. Children need not only academic skills but also leadership values, responsibility, and social awareness. This community service activity aims to educate children about leadership and the use of used materials as creative learning media. The activity was carried out at the Amsal 3 Movement Learning Center through socialization, training, educational games, and practical training in making learning materials from used materials. The results of the activity showed that the children were very enthusiastic about participating and began to understand the importance of leadership, cooperation, and environmental awareness. Furthermore, the children were able to utilize used materials as simple and useful learning materials. This activity is expected to increase children's creativity, self-confidence, and awareness of the importance of environmental protection.